Penultimate predecessors of the 2004 Indian Ocean tsunami in Aceh, Sumatra: Stratigraphic, archeological, and historical evidence. Issue 1 (18th January 2015) - Sieh, Kerry; Daly, Patrick; Edwards McKinnon, E.; Pilarczyk, Jessica E.; Chiang, Hong‐Wei; Horton, Benjamin; Rubin, Charles M.; Shen, Chuan‐Chou; Ismail, Nazli; Vane, Christopher H.; Feener, R. Michael
Abstract We present stratigraphic, archeological and historical evidence for two closely timed predecessors of the giant 2004 tsunami on the northern coast of Aceh, northern Sumatra. This is the first direct evidence that a tsunami played a role in a fifteenth century cultural hiatus along the northern Sumatran portion of the maritime silk route. One seacliff exposure on the eastern side of the Lambaro headlands reveals two beds of tsunamigenic coral rubble within a small alluvial fan. Radiocarbon and Uranium‐Thorium disequilibrium dates indicate emplacement of the coral rubble after 1344 ± 3 C.E. Another seacliff exposure, on the western side of the peninsula, contains evidence of nearly continuous settlement from 1240 C.E. to soon after 1366 ± 3 C.E., terminated by tsunami destruction. At both sites, the tsunamis are likely coincident with sudden uplift of coral reefs above the Sunda megathrust 1394 ± 2 C.E., evidence for which has been published previously. The tsunami (or tsunami pair) appears to have destroyed a vibrant port community and led to the temporary recentering of marine trade dominance to more protected locations farther east. The reestablishment of vibrant communities along the devastated coast by about 1500 CE set the stage for the 2004 disaster.